A report study of successful surgical treatment of an aorto-left ventricular tunnel in a 5-year-old boy: differential diagnosis from other congenital heart diseases with similar clinical symptoms - Alireza Yaghoubi Golverdi; Amirhossein Jalali; Mohammad Mahdavi; Seyed Salaheddin Nabavi; Mahmoud Ganjifard; Maryam Bahramian; Mozhgan Bahramian; Seyed Shervin Shafiei (The Egyptian Heart Journal)
Abstract Background Aorto-left ventricular tunnel (ALVT) is a rare congenital anomaly. In this condition, the aorto-ventricular tunnel is a congenital extracardiac channel that connects the ascending aorta to the left ventricle above the sinotubular junction. Case presentation A 5-year-old boy presented with fatigue during physical activity, leading to visiting a pediatric specialist. Upon examination, a continuous murmur, predominantly diastolic, was detected. Suspecting aortic insufficiency, the patient was referred for further evaluation. Transthoracic echocardiography revealed a congenital ALVT. Conclusion Although congenital ALVT is a rare congenital heart disease, its clinical symptoms may overlap with other congenital heart diseases, such as tetralogy of Fallot without pulmonary stenosis and patent ductus arteriosus. Differential diagnosis, such as the absence of a wide pulse pressure, can be helpful in distinguishing between these conditions.